2018
DOI: 10.1186/s40880-018-0331-y
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant transcatheter arterial chemoembolization after curative resection for hepatocellular carcinoma patients with solitary tumor and microvascular invasion: a randomized clinical trial of efficacy and safety

Abstract: BackgroundThe optimal strategy for adjuvant therapy after curative resection for hepatocellular carcinoma (HCC) patients with solitary tumor and microvascular invasion (MVI) is controversial. This trial evaluated the efficacy and safety of adjuvant transcatheter arterial chemoembolization (TACE) after hepatectomy versus hepatectomy alone in HCC patients with a solitary tumor ≥ 5 cm and MVI.MethodsIn this randomized, open-labeled, phase III trial, HCC patients with a solitary tumor ≥ 5 cm and MVI were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 51 publications
8
122
0
Order By: Relevance
“…This study identi ed 125 records through a series of PubMed searches ( Figure 2). After an initial screening of abstracts and a full-text review of the studies, 6 articles were included in the fragility analysis (Table 1, Figure 3) [6][7][8][9][10][11]. The other ve RCTs were excluded, as FI can only be calculated in RCTs that allocate 1:1 randomization (Supplementary table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study identi ed 125 records through a series of PubMed searches ( Figure 2). After an initial screening of abstracts and a full-text review of the studies, 6 articles were included in the fragility analysis (Table 1, Figure 3) [6][7][8][9][10][11]. The other ve RCTs were excluded, as FI can only be calculated in RCTs that allocate 1:1 randomization (Supplementary table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies in the fragility analysis were for primary outcome results. Three (60%) had primary outcome trials with a FI of 0 (Fisher's exact test p > 0.05), for which a strati ed log-rank test was used to calculate the reported signi cant P value [8,9,11], and these three (60%) trials had an FQ <1% [8,9,11]. The article with the highest FI fragility index of 19 was published in the Clinical Cancer Research [10].…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent meta-analysis, postoperative TACE for advanced HCC was shown to increase overall survival rate [7]. Furthermore, another study found that male patients with cirrhosis, age <60 years, tumor >10 cm, and resection margin <2 cm may derive a greater survival benefit from adjuvant TACE [8].…”
Section: Discussionmentioning
confidence: 99%
“…Using a Leica inverted research microscope (Leica Microsystems, Wetzlar, Germany), the slides were examined under 100 × magni cation to identify the highest vascular density area within the tumor, and ve representative elds were observed at a higher magni cation of 200×. Microvascular invasion (MVI) was de ned as microscopic tumor invasion identi ed in the portal or hepatic vein of the surrounding liver tissue contiguous to the tumor [23]. Tumor differentiation was histologically graded according to the Edmondson system [24].…”
Section: Outcome Measuresmentioning
confidence: 99%